Physiologic Values of Broiler Femurs at Different Growth Phases Using Bone Densitometry and Bone Breaking Strength - Barreiro , F.R.; Amaral, L.A.; Shimano, A.C.; Alva, J.C.R.; Barbosa, J.C.; Baraldi-Artoni, S.M. (International Journal of Poultry Science, 2011)
The objective of this experiment was to determine the normal values of Bone Radiographic Density (BRD) by using the optical densitometry in radiographic images and the Bone Breaking Strength (BBS) of broiler femurs at different ages (8, 22 and 42 d of age). A total of 60 Cobb male broilers were distributed in three age groups of 20 birds. The BRD and the BBS (maxim force and rigidity) values increased (p